Setting-based surveillance and One Health in the Mpox response - Marc K. Yambayamba; Simon Rüegg (One Health Outlook)
Abstract The resurgence of Mpox (MPXV) provides an opportunity to reflect on global health responses, particularly the lessons from previous outbreaks like Ebola and COVID-19. Although Mpox has been endemic in parts of Africa since the 1970s, it only gained global attention after spreading beyond Africa, highlighting the geopolitical dimension of global health. Like Ebola, Mpox is a zoonotic disease that affects both humans and animals, but the focus of the response has often been on human health, neglecting the broader social-ecological factors that influence disease transmission. A more holistic, “One Health” approach, integrating human, animal, and environmental health can help better understand the complex interactions that contribute to outbreaks. This would include surveillance of the social-ecological systems where spillover occurs and greater engagement with local communities to build trust and improve response efforts. A setting-based surveillance system, focusing on both humans and animals in their environments, would enable more accurate and efficient outbreak or pandemic prevention. Additionally, the involvement of non-health professionals, such as social scientists and community leaders, is essential for fostering locally driven, culturally sensitive response strategies. Strengthening one health systems and expanding healthcare to include animals and plants could also enhance agroecological and ecosystem resilience.